1937
DOI: 10.1508/cytologia.8.277
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Investigations of Rice Varieties

Abstract: Cytological investigations of rice varieties 279 3. 'Thekkas-chesa', obtained from Coimbatore. 4. 'Bonsari-to', obtained from Japan. 5. 'Murasaki-ine', " " " 6. 'Tanko-hoira', grown in Formosa. 7. 'Konan-sen', grown in South China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
3

Year Published

1939
1939
1980
1980

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 44 publications
0
9
0
3
Order By: Relevance
“…Binucleate and multinucleate cells have been reported in plant like Avena (Holden and Mota 1956), Gossypium (Sarvella 1958), Scilla siberica (Resss 1958), Acrolinum (Rana and Jain 1962) and Hordeum (Kamra 1960). According to Nandi (1937) and Sarvella (1958) the binucleate condition usually arises from cytomixis, while Gates and Rees (1921) and Kamra (1960) hold the view that this condition arises from the failure of cell wall formation. Beadle (1932) believed it to be genically controlled lack of cell wall formation.…”
Section: Observationsmentioning
confidence: 99%
“…Binucleate and multinucleate cells have been reported in plant like Avena (Holden and Mota 1956), Gossypium (Sarvella 1958), Scilla siberica (Resss 1958), Acrolinum (Rana and Jain 1962) and Hordeum (Kamra 1960). According to Nandi (1937) and Sarvella (1958) the binucleate condition usually arises from cytomixis, while Gates and Rees (1921) and Kamra (1960) hold the view that this condition arises from the failure of cell wall formation. Beadle (1932) believed it to be genically controlled lack of cell wall formation.…”
Section: Observationsmentioning
confidence: 99%
“…11,12,13,14,15 GEITLS~ (1934GEITLS~ ( , 1938, MATSr~:RA ), FEm~A~DES (1935, STOW (1935), USCOTT (1936), NA~DI (1937), I~ESE~DE (1936 Naeh LEvA~ sollen bei natiirliehen Arten BuibiIten nur auf Polyploiden auftreten (vgl. auch MESSEm, 1930;TURESSON, 1930TURESSON, , 1931L~JEFO~S, 1934L~JEFO~S, und 1935.…”
Section: T~mistokles Diani#elidisunclassified
“…In the case of the terminal type a nucleolus-organizing body consisted of heterochromatin is either present or absent and the former is found in some plants such as Narcissus bulbocodiam var. genuinus (Fernandes 1935) and Oryza sativa (Nandi 1937) and the latter in other plants such as Trillium ka ntscha,ticuna (Matsuura 1938) and Paris hexaphulla (Haga 1940;Sato 1941). In the case of the interstitial type it is reported that not only a stalk of so called SAT-chromosome (satellited chromosome, chromosome with a secondary constriction) includes thymonucleic acid, but also primary constriction's participate in nucleolus organization in some samples.…”
Section: Introductionmentioning
confidence: 99%